NUMBERS AND CHRONICLES OF MULTIPLE MYELOMA INCIDENCE MORTALITY AND PREVALENCE ACROSS REGIONS: REVIEW OF THE LITERATURE WITH SEER DATA ANALYSIS - Mateusz Kęska; Michael Platschek; Anna Barbara Tuleja; Michał Drabik; Julia Kosmulska; Klaudia Dybalska; Maksym Sikora; Sylwia Wiktoria Kolano; Jakub Nowak; Karol Józef Szkarłat; Illia Lastovetskyi (International Journal of Innovative Technologies in Social Science, 2025)
Global and regional data reveal a sustained rise in incident and prevalent multiple myeloma with crude deaths increasing through population ageing, while age standardized mortality has remained broadly stable. Men are affected more than women and ancestry strongly shapes risk, with the highest incidence and mortality in Black populations and the lowest in Asian and Pacific Islander groups. East Asia shows the fastest proportional growth, whereas the absolute burden is greatest in high income regions. Presentation remains dominated by organ damage and advanced stage in several Middle Eastern and African cohorts. Survival has improved across periods and age groups with wider use of proteasome inhibitors, immunomodulatory agents, autologous transplantation and anti CD38 antibodies, though early mortality persists in the oldest patients and outcomes vary by site and capacity of care. High body mass index is the only quantified modifiable contributor in global attribution analyses. Survivorship includes a measurable risk of second primary malignancies, enriched for hematologic cancers. Forecasts to mid century attribute most growth to demographics and anticipate increases in cases and deaths despite stable or falling age standardized rates in some settings. Treated epidemiology is shifting toward earlier use of lenalidomide and anti CD38 therapy, rising double refractoriness, and attrition between lines, highlighting the need for timely diagnosis, infection and renal management, equitable access, and planning for advanced immunotherapies.